Electrocatalytic oxidation of Pd/Ti anode for the treatment of reverse osmosis concentrates from coking wastewater - YIN Xing; GUO Yun; REN Lehui; WANG Xueye; WANG Zhiwei* (能源环境保护)
In this study, a Pd -loaded porous titanium anode was prepared using a simple spraying method, and an electrocatalytic oxidation system was constructed with Pd/Ti as anode and titanium mesh as cathode to achieve the efficient and stable removal of refractory organic pollutants from coking wastewater reverse osmosis concentrates. At a current density of 5 mA/cm^2, the Pd/Ti anode achieved a COD removal of 86.3% in 4 hours which was higher than that of the BDD (46.7%) and Ir/Ta (34.0%) electrodes. Gas chromatography-mass spectrometer analysis demonstrated that the electrocatalytic system with Pd/Ti as the anode could effectively convert refractory organic pollutants (e.g., 1,2-dimethyl-5-nitroadamantane) in the reverse osmosis concentrate into simple substances (e.g., 2-pentyn-1-ol). During the 28-hour long-term operation, the COD effluent was less than 50 mg/L, meeting the limit of the standard for direct discharge of wastewater in the Emission Standard for Pollutants in Coking Chemical Industry (GB 16171—2012). These results indicated that the Pd/Ti anode had the potential for eliminating refractory organic pollutants in reverse osmosis concentrates from coking wastewater with high efficiency and low consumption.